Social Behavior Analysis Theory of Children in the Transition Period from Home to School: Studi Literature Review - Ningrum, Sri Utami; Dwi Utami, Ade; Sumadi, Tjipto (JURNAL PENDIDIKAN USIA DINI, 2024)
This study aims to identify and analyze the social behavior of children during the transition from home to school environments. The study utilizes a literature review method encompassing the ELSEVIER, Sage Journals, ResearchGate, and Taylor & Francis databases. It examines various literature on children's social behavior during the transition period, the role of parents, and the role of teachers during the transition from home to school. The findings of this review are contextualized within the broader framework of early childhood social behavior. The research findings indicate that while a number of studies have investigated children's social behavior during the transition period, there is still a lack of comprehensive empirical understanding. This study highlights the need for further research that focuses on a comprehensive understanding of children's social behavior during this transition period to support optimal social and academic development in children. Furthermore, this study also emphasizes the importance of intervention strategies that can help children navigate environmental changes more effectively.